Cisco CCNP Collaboration CLCOR v1.2 (350-801) Cert Prep. - Wallace, Kevin (linkedin.com, 2024)
Get an introduction to Cisco Collaboration technologies and concepts in alignment with the first portion of the Cisco CCNP Collaboration (350-801) CLCOR v1.1 exam.